Strategi Coping Stress pada Orang Tua Anak Berkebutuhan Khusus - Daniel Simanjuntak; Suryanto Suryanto; Wiwin Hendriani (Humanitas (Jurnal Psikologi), 2026)
Parents of children with special needs are particularly vulnerable to psychological stressors such as anxiety, sleep disturbances, and frustration, making the selection of appropriate coping strategies essential for managing caregiving challenges. This study aimed to identify and describe the coping strategies commonly used by parents of children with special needs and to examine protective factors that support parental well-being. A descriptive qualitative design was employed, with three participants who were mothers of children with special needs. Findings indicate that participants primarily utilized emotion-focused and problem-focused coping strategies to address caregiving demands. Two protective factors, social support and the parent-child relationship were identified as instrumental in reducing negative emotional impact and sustaining caregiving efforts. The study’s findings contribute to understanding coping processes among parents of children with special needs and may serve as a reference for future research and interventions aimed at enhancing parental resilience.